Cherenko Makar Petrovych. To the 100th anniversary of his birth - Markulan, L.Y. (General Surgery, 2025)
The biographical essay is dedicated to the outstanding Ukrainian surgeon, one of the founders of thyroid surgery in Ukraine, Honored Worker of Science and Technology, laureate of the State Prize of Ukraine in Science and Technology, Professor Makar Petrovych Cherenko – whose life and work became a model of devotion, humanism, and exceptional professional mastery. The essay presents the key milestones of his biography, scientific achievements, pedagogical and public activity, as well as his contribution to the formation of the Ukrainian surgical school.